Optimal timing of anticoagulation after acute ischaemic stroke with atrial fibrillation (OPTIMAS): statistical analysis plan for a randomised controlled trial - Norin Ahmed; Hakim-Moulay Dehbi; Nick Freemantle; Jonathan Best; Philip S. Nash; James K. Ruffle; David Doig; David J. Werring (Trials)
Abstract Background Atrial fibrillation causes one-fifth of ischaemic strokes, with a high risk of early recurrence. Although long-term anticoagulation is highly effective for stroke prevention in atrial fibrillation, initiation after stroke can be delayed by concerns over intracranial haemorrhage risk. Direct oral anticoagulants offer a significantly lower risk of intracranial haemorrhage than other anticoagulants, potentially allowing earlier anticoagulation and prevention of ischaemic stroke recurrence, but the safety and efficacy of this approach has not been established. This article describes the statistical analysis plan for the OPTIMAS trial as an update to the published protocol. It was written prior to the end of patient follow-up, before database lock and thus while the outcome of the trial is still unknown. Aim The optimal timing of anticoagulation after acute ischaemic stroke with atrial fibrillation (OPTIMAS) trial will investigate whether early treatment with a direct oral anticoagulant within 4 days of stroke onset is as effective as, or better than, delayed initiation at 7 to 14 days from onset. Methods and design OPTIMAS is a multicentre randomised controlled trial with blinded outcome adjudication. Participants with acute ischaemic stroke and atrial fibrillation eligible for anticoagulation with a direct oral anticoagulant are randomised 1:1 to early or delayed initiation. Here, we describe in detail the statistical aspects of OPTIMAS, including outcome measures, sample size calculation, general analysis principles, descriptive statistics, statistical models, and planned subgroup analyses. Study outcomes The primary outcome is a composite of recurrent stroke (ischaemic stroke or symptomatic intracranial haemorrhage) and systemic arterial embolism within 90 days. Secondary outcomes include each individual component of the composite outcome, major bleeding, functional status assessed by the modified Rankin Scale, ongoing anticoagulation, quality of life, health and social care resource use, and length of hospital stay. Discussion OPTIMAS aims to provide high-quality evidence on the safety and efficacy of early direct oral anticoagulant initiation after atrial fibrillation-associated acute ischaemic stroke. Trial registrations ISRCTN: 17,896,007; ClinicalTrials.gov: NCT03759938. Registered on November 30 2018.